2021
DOI: 10.1007/s11249-021-01463-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Base oil Polarity on the Tribological Performance of Surface-Active Engine Oil Additives

Abstract: Friction, wear and tribo lm growth of organic friction modi ers (glycerol monooleate and oleamide), antiwear additive (ZDDP) and binary additive system comprising the organic friction modi ers and ZDDP were studied in polyalphaole n (PAO) and ester oil. The mechanisms underlying base oil polaritydependent frictional performance of the OFM and AW additives at high temperature (140 oC), either singly or in combination, was investigated in the light of chemical composition analysis of the tribo lms post friction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 62 publications
1
15
0
1
Order By: Relevance
“…Researchers 36 state that some of the degradation occurring in the lubricants is below the detectable limit of FTIR. Therefore, the oils were subjected to ESR spectroscopy for further analysis.…”
Section: Ftir Analysismentioning
confidence: 99%
“…Researchers 36 state that some of the degradation occurring in the lubricants is below the detectable limit of FTIR. Therefore, the oils were subjected to ESR spectroscopy for further analysis.…”
Section: Ftir Analysismentioning
confidence: 99%
“…38 Many studies demonstrated that high adsorbed masses or thick films result in low friction and wear, possibly due to the high surface coverage and packing density. 17,20,43 In contrast, a few recent studies reported that adsorbed masses evidently affect the initial friction but not the steady-state friction, 30 and fast adsorption kinetics is effective at reducing friction and wear rather than high adsorbed masses. 35 A recent study also suggests that complete surface coverage is not necessary for effective friction reduction.…”
Section: Introductionmentioning
confidence: 97%
“…The adsorption kinetics depends on the chemical structure of not only the functional groups and alkyl chains of OFMs but also of lubricating oils because adsorption involves a process of OFM molecules diffusing onto the solid surfaces from the lubricating oils. , The literature shows that, on ferrous substrates, OFMs with carboxylic acid and amine groups are generally more effective than with alcohol and ester groups. , It was reported that, compared with a single functional group, multiple functional groups lead to strong adsorption owing to the multisite adsorption or chelate effect and thereby high adsorbed masses; however, the steric hindrance caused by the large size could slow down the adsorption kinetics. , Longer alkyl chains were found to result in thicker boundary films, , and linear saturated alkyl chains are believed to result in ordered and close-packed boundary films compared with branched and unsaturated ones . Many studies demonstrated that high adsorbed masses or thick films result in low friction and wear, possibly due to the high surface coverage and packing density. ,, In contrast, a few recent studies reported that adsorbed masses evidently affect the initial friction but not the steady-state friction, and fast adsorption kinetics is effective at reducing friction and wear rather than high adsorbed masses . A recent study also suggests that complete surface coverage is not necessary for effective friction reduction .…”
Section: Introductionmentioning
confidence: 99%
“…6 The frictional performance of OFM is shown to be a function of its molecular structure and external factors such as load, temperature, sliding speed, nature of solvent and substrate material. 1,2,[7][8][9][10][11][12] Glycerol Mono-oleate (GMO) and oleamide are the most commonly used OFMs. 13,14 Even though they are effective in reducing friction, the boundary films formed by them can be brushed off under harsh contact conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The contrasting result suggests that these surface-active molecules are effective under specific operating conditions. 12 The most commonly used organo-molybdenum compounds are molybdenum dialkyldithiophosphate and molybdenum dialkyldithiocarbamate. 18 Even though they are effective in reducing friction, they can produce hazardous lubricant discharge and therefore are not environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%